2017
DOI: 10.1016/j.coviro.2017.07.017
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus: a master epigenetic manipulator

Abstract: Like all herpesvirus, the ability of Epstein-Barr virus (EBV) to establish life-long persistent infections is related to a biphasic viral lifecycle that involves latency and reactivation/lytic replication. Memory B cells serve as the EBV latency compartment where silencing of viral gene expression allows maintenance of the viral genome, avoidance of immune surveillance, and life-long carriage. Upon viral reactivation, viral gene expression is induced for replication, progeny virion production, and viral spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 83 publications
1
41
0
Order By: Relevance
“…EBV infection leads to the epigenetic changes, involving DNA methylation and histone modifications, and signaling pathway aberrations in host cells 8 , 46 . Our transcriptome analysis revealed that vasculogenesis-related genes were upregulated in EBV-infected epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection leads to the epigenetic changes, involving DNA methylation and histone modifications, and signaling pathway aberrations in host cells 8 , 46 . Our transcriptome analysis revealed that vasculogenesis-related genes were upregulated in EBV-infected epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…After EBV infection of host cells, these EBV miRNAs form incomplete complementary pairing with the 3'-untranslated region (3'UTR) of the virus's own genes or host gene mRNAs, resulting in inhibition of gene translation or the degradation of targeted mRNAs [37]. In recent years, many studies have shown that EBV miRNAs can inhibit the expression and presentation of viral antigens by inhibiting the expression of viral genes and host cell genes, inhibiting the activation and cytotoxicity of immune cells, and achieving long-term latency, immune escape, and promotion of host cells immortalization and tumor development [38], which is briefly reviewed below.…”
Section: Ebv Mirnasmentioning
confidence: 99%
“…We also show that downregulation of KDM2B expression in EBV-infected cells is mediated by DNMT1 recruitment to its gene and by its DNA methylation. It has already been reported that EBV can alter DNMT1 activity through its viral proteins LMP1 and LMP2A (29). In particular, Tsai and colleagues showed that LMP1 activates DNMT1 activity (15) and that this event requires activation of the JNK/AP1 pathway.…”
Section: Discussionmentioning
confidence: 99%